Pathophysiological role of BACH transcription factors in digestive system diseases - Song, Qianben; Mao, Xin; Jing, Mengjia; Fu, Yu; Yan, Wei (Frontiers in Physiology, 2023)
BTB and CNC homologous (BACH) proteins, including BACH1 and BACH2, are transcription factors that are widely expressed in human tissues. BACH proteins form heterodimers with small musculoaponeurotic fibrosarcoma (MAF) proteins to suppress the transcription of target genes. Furthermore, BACH1 promotes the transcription of target genes. BACH proteins regulate physiological processes, such as the differentiation of B cells and T cells, mitochondrial function, and heme homeostasis as well as pathogenesis related to inflammation, oxidative-stress damage caused by drugs, toxicants, or infections; autoimmunity disorders; and cancer angiogenesis, epithelial-mesenchymal transition, chemotherapy resistance, progression, and metabolism. In this review, we discuss the function of BACH proteins in the digestive system, including the liver, gallbladder, esophagus, stomach, small and large intestines, and pancreas. BACH proteins directly target genes or indirectly regulate downstream molecules to promote or inhibit biological phenomena such as inflammation, tumor angiogenesis, and epithelial-mesenchymal transition. BACH proteins are also regulated by proteins, miRNAs, LncRNAs, labile iron, and positive and negative feedback. Additionally, we summarize a list of regulators targeting these proteins. Our review provides a reference for future studies on targeted drugs in digestive diseases.